Pemberdayaan Komunitas Kampung Film Bulusari melalui Pelatihan Produksi Film Pendek dan Penguatan Manajemen Kreatif - Yusro Edy Nugroho; Siti Hadiati Nugraini; Asep Purwo Yudi Utomo; Inna Havidatus Saniyah; Indri Dwi Astuti; Wastu Bondan Susantiyanto (Pusat Riset dan Inovasi Nasional, 2026)
The Bulusari Film Village Community possesses considerable potential as a community-based creative space, yet it continues to face limitations in technical film production skills and community management. This community engagement program aims to strengthen the community’s creative capacity and professionalism through training in scriptwriting, cinematography, production, and film editing, as well as reinforcing organizational management using the Participatory Community Appraisal (PCA) approach. The activities were implemented through five major stages, namely needs identification, formulation of alternative solutions, technical training, short film production mentoring, and strengthening of the community’s management system. The results demonstrate significant improvements in members’ technical competencies across all stages of film production, from pre-production to post-production. The community successfully produced a script and one short film with enhanced visual and narrative quality compared to their earlier works. In addition, the establishment of a new organizational structure, operational SOPs, and a simple administrative system effectively improved community governance. The program also broadened the community’s collaborative network with local government, educational institutions, and other creative groups. These findings indicate that PCA-based empowerment supports increased creativity, autonomy, and competitiveness among local creative communities in alignment with the SDGs, particularly SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 11 (Sustainable Communities).